FAKTOR-FAKTOR YANG MEMPENGARUHI PATOGENITAS TRICHOMONAS VAGINALIS - Azahra, Sresta; Susanto, Lisawati (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Trichomonas vaginalis is a flagellated protozoan parasite that causes trichomoniasis. Trichomoniasis is a non-viral sexually transmitted infection and is found in the human urogenital tract. The interaction between T. vaginalis with the host is very complex and many factors influence the pathogenicity of T. vaginalis. To determine the factors that influence the pathogenicity of Trichomonas vaginalis. Literature review using the Google Scholar database. The search results for articles matched the criteria with the keyword